Always-on mobile phone behaviour impulsive and postmodern consumers. (19th April 2011) - Altintas, M. Hakan; Gursakal, Necmi; Kaufmann, Hans Ruediger; Vrontis, Demetris; , Feride Bahar Isin
This paper investigates the antecedents of addictive-based mobile phone behaviour; a new phenomenon in mobile phone consumption. Specifically, it examines the effects of impulsive behaviour and post-modern consumer behaviour on the addiction of young consumers to mobile phones, which is reflected in leaving their cell phones switched on for 24 hours per day. This study has been conducted on 450 consumers from the cities of Bursa and Istanbul, Turkey. The results imply that post-modern consumer behaviour has a positive effect on all aspects of the addictive pattern of always-on behaviour, whereas impulsive behaviour has only a partial effect. Unreal world dimensions of postmodern consumer behaviour have a positive effect on addictive behaviour. Also, sensation-seeking, which is a part of the impulsive behaviour dimension, was assessed to have an effect on continuous connectivity. According to the knowledge of the authors this is the first interdisciplinary study explaining the antecedents of addictive mobile phone behaviour of young consumers. The innovative findings of the study are suggested to inform, besides other marketing related studies, also sociological and psychological studies on the identity and roles of young citizens in the society.